2021
DOI: 10.1177/0022034521990653
|View full text |Cite
|
Sign up to set email alerts
|

Third-Molar Status and Risk of Loss of Adjacent Second Molars

Abstract: The prophylactic removal of asymptomatic third molars is a common but controversial procedure often rationalized as necessary to prevent future disease on adjacent teeth. Our objective in this retrospective cohort study of adult men was to examine whether second-molar loss differed by baseline status of the adjacent third molar, taking into account the individual’s overall state of oral hygiene, caries, and periodontitis. We analyzed data from participants of the VA Dental Longitudinal Study who had at least 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
6
0
2
Order By: Relevance
“…The removal of third molars is one of the most commonly performed surgical procedures in oral surgery. Recent guidelines recommend the removal of pathologically erupting third molars in order to prevent future complications 1 , 2 . The second molar is frequently disrupting the eruption path of the third molar, evoking it to only erupt partially or not at all, which can adversely affect periodontal health of the second molar.…”
Section: Introductionmentioning
confidence: 99%
“…The removal of third molars is one of the most commonly performed surgical procedures in oral surgery. Recent guidelines recommend the removal of pathologically erupting third molars in order to prevent future complications 1 , 2 . The second molar is frequently disrupting the eruption path of the third molar, evoking it to only erupt partially or not at all, which can adversely affect periodontal health of the second molar.…”
Section: Introductionmentioning
confidence: 99%
“…Aynı şekilde bu dişlerin etrafında ameloblastik ya da neoplastik kitle görülme ihtimalinin %1'den az olduğu belirtilmiştir. 20,21 Bu oranların, asemptomatik üçüncü molar dişlerde profilaktik çekim kararı alınabilmesi için yeterli olmadığını düşünmekteyiz. Çalışmamızda kist-tümör oluşumu sebebiyle çekim endikasyonu koyulan dişler tüm çekilen dişlerin %7.51'ini oluştururken, profilaktik olarak çekilen dişlerin oranı %1.98'dir.…”
Section: Discussionunclassified
“…Compared with M2s without neighboring M3s, retained impacted M3s have been confirmed to increase the risk of M2 pathology by 2.16- to 4.88-fold [ 11 ]. Interestingly, Kaye and colleagues recently reported that retained M3s were not associated with an increased risk of M2 loss among adult men (average age: 48 years) [ 39 ]. Their study excluded participants whose M2s were already extracted, and this leads us to the opposite conclusion.…”
Section: Discussionmentioning
confidence: 99%